Fan-Out Wafer-Level Packaging - Lau, John H. (Springer Singapore, 2018)
This comprehensive guide to fan-out wafer-level packaging (FOWLP) technology compares FOWLP with flip chip and fan-in wafer-level packaging. It presents the current knowledge on these key enabling technologies for FOWLP, and discusses several packaging technologies for future trends. The Taiwan Semiconductor Manufacturing Company (TSMC) employed their InFO (integrated fan-out) technology in A10, the application processor for Apple's iPhone, in 2016, generating great excitement about FOWLP technology throughout the semiconductor packaging community. For many practicing engineers and managers, as well as scientists and researchers, essential details of FOWLP - such as the temporary bonding and de-bonding of the carrier on a reconstituted wafer/panel, epoxy molding compound (EMC) dispensing, compression molding, Cu revealing, RDL fabrication, solder ball mounting, etc. - are not well understood. Intended to help readers learn the basics of problem-solving methods and understand the trade-offs inherent in making system-level decisions quickly, this book serves as a valuable reference guide for all those faced with the challenging problems created by the ever-increasing interest in FOWLP, helps to remove roadblocks, and accelerates the design, materials, process, and manufacturing development of key enabling technologies for FOWLP.